The assessment of applicability of single-stage piston long-stroke low-speed compressors in low-temperature refrigeration machines - V. L. Yusha; S. S. Busarov; A. V. Nedovenchany (Омский научный вестник: Серия "Авиационно-ракетное и энергетическое машиностроение")
The work processes and integral characteristics of low-temperature ammonia single-stage piston longstroke low-speed compressors are considered. A method for calculating the actual working process of a stage of such a compressor is presented, taking into account such basic factors as the processes of non-stationary heat transfer between the working fluid in the cylinder and the external cooling medium; processes of flow of the working fluid through leaks in valves and in seals of the cylinder-piston group; dynamics of motion of the shut-off valve body, etc. The flow coefficient, cooling coefficient, and discharge temperature are considered as integral indicators. The following independent parameters are considered: condensation and boiling temperatures, the main dimensions and parameters of the stage, the temperature of the cooling medium and the heat transfer coefficient on the outer surface of the cylinder, as well as the diameters of the suction and discharge valve seats. A comparative analysis of the efficiency of the working process of the considered stage is performed at a condensation temperature of 303 K and boiling temperatures in the range from 243 K to 173 K. The relationship between the main dimensions and parameters of the stage, as well as the boiling point of ammonia with the integral characteristics of the compressor under consideration, has been studied. The obtained results of the theoretical analysis make it possible to evaluate the possibility of replacing multi-stage and cascade low-temperature refrigeration compressors with alternative single-stage ones based on a low-speed, long-stroke stage as promising.